PENGARUH BENTUK TES FORMATIF DAN KEMAMPUAN AWAL SISWA MADRASAH TERHADAP HASIL BELAJAR MATEMATIKA - Farida Hanun (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2009)
This research is aimed at identiffing the effect of formative assessment in improving the results of study of students on mathematics lesson interconnected with the initial ability of students. The research was conducted at MAN 9 in DKI Jakarta in the second semester of 2007-2008 academic year. The sample was selected by applying simple random sampling technique and the site was 80.This research used experiment method with factorial design 2 x 2 and the data were analyzed by using Two-way Anova and T- test at/the level of significance a = 0,05.